Effect of Covid-19 Pandemic on Economic Growth in the World - Ghaleb, Belal Dahiam Saif (PT. Riset Press International, 2024)
As national borders diminish in significance due to globalization, interdependence between countries has intensified. Covid-19 emerged as an acute respiratory disease in Wuhan, China in December 2019 and spread to all countries of the world in a short time. In this study, information is given about the concepts, developments, general impact, and impact on economic growth in the international market about Coronavirus. During the pandemic process, the issue of economic growth was researched, its increase and decrease were examined and analyzed. The aim of the study is to investigate the effects of the Covid-19 pandemic on economic growth in the world labor markets and to reveal the general situation in the world by analyzing the available data in the literature.